The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1007/s11373-007-9230-y
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional factor Snail simultaneously triggers cell cycle arrest and migration of human hepatoma HepG2

Abstract: Snail was recently highlighted as a critical transcriptional factor for tumor metastasis. Real time RT/PCR and Western blot analysis demonstrated that Snail mRNA and protein, respectively, were induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) in hepatoma cell HepG2. Blockade of gene expression of Snail by antisense oligodeoxynucleotide and/or siRNA technique can prevent not only the TPA-triggered EMT/cell migration and growth inhibition of HepG2 but also TPA-induced down-regulation of E-cadherin and up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Because TPA has been reported to induce EMT-like cell scattering in HepG2 cells [27], we used U0126 to determine whether ERK1/2 activation was responsible for this process. In control conditions, HepG2 cells had an epithelial cell-like morphology with a characteristic “cobblestone” appearance and the organization of F-actin into a cortical pattern at cell-to-cell junctions (Figure 1B, arrowhead).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because TPA has been reported to induce EMT-like cell scattering in HepG2 cells [27], we used U0126 to determine whether ERK1/2 activation was responsible for this process. In control conditions, HepG2 cells had an epithelial cell-like morphology with a characteristic “cobblestone” appearance and the organization of F-actin into a cortical pattern at cell-to-cell junctions (Figure 1B, arrowhead).…”
Section: Resultsmentioning
confidence: 99%
“…Previous study had shown that the EMT triggered by TPA is dependent on Snail [27]. Accordingly, we sought to determine if ERK1/2 was responsible for the Snail activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Snail also triggers migration of hepatoma HepG2, 37 and oesophageal squamous cell carcinoma cells. 38 Snail silencing dramatically reduced the ability of breast carcinoma MDA-MB231 cells to migrate into collagen IV.…”
Section: The Role Of Snail In Cell Migrationmentioning
confidence: 99%
“…Accordingly, the transcription factor and EMT inducer Snail simultaneously triggers cell cycle arrest and migration of human hepatoma HepG2 by inducing p15 Ink4B . 64 An argument against this notion can be seen with the treatment of primary mouse hepatocytes deficient in p53, p21 CIP1/ WAF1 and/or Rb (singly or in combination) with TGFβ. These cells show a similar induction of EMT-morphological changes regardless of genotype and independent of proliferation index.…”
Section: A Link Between Early Failsafe Program Escape and Cancer Cellmentioning
confidence: 99%